2008
DOI: 10.1192/apt.bp.107.003509
|View full text |Cite
|
Sign up to set email alerts
|

Individual placement and support: from research to practice

Abstract: Vocational rehabilitation for people with severe mental health problems is poorly developed in the UK.Although there is a clear evidence base indicating the effectiveness of approaches to helping people with severe mental health problems gain and retain employment there is generally a lack of awareness of this evidence. As a result there has been a lack of implementation within routine clinical practice of the most effective approaches to improving employment outcomes for such individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 65 publications
1
65
0
7
Order By: Relevance
“…[27][28][29][30][31][32][33][34] Vocational support programmes that include inter agency collaboration and adhere to the individual placement and support (IPS) model with the use of an integrated community employment specialist, have been shown to be most effective in helping those with mental health disabilities gain and sustain employment, and should form part of any psychiatric rehabilitation service. 35 …”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34] Vocational support programmes that include inter agency collaboration and adhere to the individual placement and support (IPS) model with the use of an integrated community employment specialist, have been shown to be most effective in helping those with mental health disabilities gain and sustain employment, and should form part of any psychiatric rehabilitation service. 35 …”
Section: Discussionmentioning
confidence: 99%
“…The mental health field appears to be in the grips of conflicting and competing paradigms (Corrigan & McCracken, 2005;Rinaldi et al, 2008). There has long been a biomedical-oriented perspective that uses a "train then place" model, with the expected trajectory being: "The illness is decisive for first care, then treatment, and later on rehabilitation, and possibly vocational rehabilitation" (Bejerholm, Larsson, & Hofgren, 2011, p. 60).…”
Section: Conflicting Paradigmsmentioning
confidence: 99%
“…Various factors have been identified that contribute to the difficulties that people with mental health problems face in finding and keeping employment in the UK. These include the low expectations of healthcare professionals and a poorly developed vocational rehabilitation service (Rinaldi 2008). People also face structural barriers (such as potential loss of welfare benefits), stigma and stress in the workplace and fear of disclosure of mental ill health to employers (Bevan 2013).…”
Section: Articlementioning
confidence: 99%
“…patients who feel they are ready for paid employment (Crowther 2001;Rinaldi 2008;Kinoshita 2013). A European randomised controlled trial demonstra ted that IPS was successful at getting 55% of people back into open employment (Burns 2008).…”
Section: Declaration Of Interestmentioning
confidence: 99%
See 1 more Smart Citation